Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian di Seedy Coffee Kota Samarinda - Widodo, Reza; Noor Andriana, Ana (Jurnal Etnik: Ekonomi-Teknik, 2022)
Coffee has long been universally traded and has occupied a position of value for the world's population. In the business world, the problem that often occurs is that competition is getting stronger and tighter, so that every business person is required to be able to optimize their business performance in order to increase the competitiveness of their products in the market. There are several advantages in the competition of a business is in terms of price and quality. So that consumers are faced with choices from competing products with varying prices. The purpose of this study was to examine the effect of price and product quality on purchasing decisions. SPSS Statistics version 20 is software that is used to help analyze data, namely multiple linear regression. The type of research used in this research is associative quantitative research which has the aim of knowing the effect of two or more variables. Sampling in this study used probability sampling technique with the type of simple random sampling and obtained a total sample of 91 respondents. Data collection techniques using questionnaires and literature. The hypothesis of this research is the influence of price and product quality on purchasing decisions at Seedy Coffee, Samarinda City. The results of the analysis of the F test of 17,170 thus the price and product quality have a significant simultaneous effect on purchasing decisions, while the price has a partial effect on purchasing decisions with the value of the t test results (X1) 3,596, and product quality has no partial effect on purchasing decisions with a value of t test results (X2) 0.362.